2021
DOI: 10.1111/jfd.13503
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between genome sequences of Chilean Tenacibaculum dicentrarchi isolated from red conger eel (Genypterus chilensis) and Atlantic salmon (Salmo salar) focusing on bacterial virulence determinants

Abstract: All genome sequencing data have been deposited in GenBank.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 146 publications
(183 reference statements)
0
27
0
Order By: Relevance
“…Resistance‐related determinants identified included tetracycline (translation elongation factor G‐WP_101916661 and tetracycline resistance protein TetQ‐WP_101917382), fluoroquinolones (gyrA‐WP_193706303 and gyrB‐WP_193706307), betalactamases (metal‐dependent hydrolases of the beta‐lactamase superfamily I‐WP_101916599) and triclosan and isoniazid (fabV‐WP_101916498). Excepting fabV , all of these genes were previously identified in T. dicentrarchi (Saldarriaga‐Córdoba et al., 2021). RAST analysis also identified genes associated with resistance to toxic compounds (e.g.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Resistance‐related determinants identified included tetracycline (translation elongation factor G‐WP_101916661 and tetracycline resistance protein TetQ‐WP_101917382), fluoroquinolones (gyrA‐WP_193706303 and gyrB‐WP_193706307), betalactamases (metal‐dependent hydrolases of the beta‐lactamase superfamily I‐WP_101916599) and triclosan and isoniazid (fabV‐WP_101916498). Excepting fabV , all of these genes were previously identified in T. dicentrarchi (Saldarriaga‐Córdoba et al., 2021). RAST analysis also identified genes associated with resistance to toxic compounds (e.g.…”
Section: Resultsmentioning
confidence: 88%
“…Regarding the stress response (e.g. osmotic, oxidative and periplasmic stress), the Chilean T. piscium isolates and type strain displayed the same genes identified in T. dicentrarchi (Supplementary Table 2) (Saldarriaga‐Córdoba et al., 2021).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…infections. The current treatments of choice for tenabaculosis caused by T. dicentrarchi in farmed salmon are oral FFC and injectable OTC (Saldarriaga‐Córdoba et al., 2021). Of these, injectable OTC has obtained the best field results.…”
Section: Resultsmentioning
confidence: 99%
“…DN‐00432/2021, March 12th, 2021) leave FFC as the only treatment alternative. In addition, a recent genomic study comparing gene features found in Atlantic salmon and red conger eel isolates have denoted that eight T. dicentrarchi isolates possess genes related to tetracycline resistance (Saldarriaga‐Córdoba et al., 2021).…”
Section: Resultsmentioning
confidence: 99%